إضاءة على مشروع قانون إصلاح نظرية المسؤولية المدنية في التشريع المدني الفرنسي الحديث: المبررات والنتائج - عرفان الخطيب, محمد (جامعة الوادي University of Eloued, 2019)
ملخص عربي تقدم الورقة البحثية إضاءة قانونية لمشروع قانون إصلاح نظرية أحكام المسؤولية المدنية 2017"، Projet de Réforme du droit de la responsabilité civile «Urvoas» 2017، الممهد لتعديل أحكام هذه المسؤولية في التشريع المدني الفرنسي، وذلك وفق منهج بحثي مقارن يُبين الدوافع والمبررات التي دفعت المشرع الفرنسي لطرح هذا المشروع، والنتائج القانونية المرتقبة لتبنيه في الإطار العام لنظرية المسؤولية المدنية. عارضين لموقف المشرع الفرنسي من هذه النظرية في القانون المدني السابق والحالي مقارنةً مع نظيره الاستشرافي في مشروع القانون الحالي. بهدف منح رجال القانون والفقه العرب إضاءة أكثر قرباً لهذا المشروع. كما استبيان مدى نجاح واضعيه، في إعادة الاعتبار القانوني لهذه النظرية وتصويب مختلف الجوانب السلبية التي كانت تعاني منها. كل ذلك عبر محورين رئيسين يشكلان قسمي هذه الدراسة، الأول: يُبين المبررات التي دفعت المشرع الفرنسي لطرح هذا المشروع "المطلب الأول". والثاني يُبين النتائج المحتملة التي ستترتب على تبني هذا المشروع على الإطار العام لهذه النظرية "المطلب الثاني". وقد بَيَّنَ البحث أوجه القصور التي تعاني منها هذه النظرية في الجانب التقنيني والتطبيقي، إنْ على المستوى الوطني أو على المستوى المقارن، ما أفقدها الكثير من طبيعتها التقنينة، وبريقها التنافسي. مبعداً الأنظار عنها لمنظومات قانونية أخرى أكثر تكييفاً مع الواقع، وأكثر استجابة لمتغيراته القانونية والاقتصادية، لاسيما الأنكلوسكسونية منها. وقد خلص البحث، بأن هذه الخطوة التشريعية، حال تبينها، ستعالج العديد من أوجه القصور والخلل التي تعاني منها نظرية المسؤولية المدنية في التشريع المدني الفرنسي، شكلاً وموضوعاً. حيث أثبتت الدراسة التحليلية للمشروع، أن منهجيته الشكلية ستساعد في التأسيس لنظرية قانونية في المسؤولية المدنية، مكتملة الجوانب والأركان إلى حد كبير، مبرزةً تبويباً قانونياً أكاديمياً ممنهجاً يوضح مختلف مراحل هذه المسؤولية. كما بَيَّنَ البحث، كيف سيمنح البناء الموضوعي للمشروع، وجوداً موضوعياً مستقلاً لهذه النظرية، منفصلاً عن كل من نظرية الالتزام، التي كانت تستوعبها في القانون المدني السابق، ونظرية العقد التي لا تزال تمتزج معها في القانون المدني الحالي. ِEnglish Abstrac This paper presents a Legal lighting on the bill reforming the theory of civil responsibility 2017, "Projet de Réforme du droit de la responsabilité civile «Urvoas» 2017", which is designed to modify the provisions of this responsibility in the French civil legislation, according to a comparative research methodology that shows the motives and justifications that prompted the French legislator to present this project and the expected legal results to adopt it in the general framework of civil responsibility theory. In this respect, we display the position of the French legislator on this theory in the previous and current civil laws, compared with his forward-looking counterpart in the current bill, in order to give the Arab jurists and jurisprudents closer lighting to this project. In addition, this paper aims to investigate the extent of the success of its authors to restore the legal consideration of this theory and correct the various negative aspects that it suffered from. All these steps are approached through two main axes that form the two parts of this study. The first shows the rationale that prompted the French legislator to put forward this project "first section". The second shows the potential consequences of the adoption of this project on the general framework of this theory, "second section". The research showed the shortcomings of this theory in the normative and applied aspects, whether at the national level or at the comparative level. It has lost much of its technical nature, and its competitive luster to other legal systems that are more adapted to reality, and more responsive to its legal and economic changes, especially the Anglo-Saxon ones. The research concluded that this legislative move, if it is adopted, will address many of the shortcomings and defects of the civil responsibility theory in the French civil law, both in form and subject matter. The analytical study of the project proved that its formal methodology will help to establish a legal theory of the civil responsibility, integrated with aspects and elements to a large extent, highlighting a legal and systematic legal tabulation explaining the various stages of this responsibility. The research also examines how the objective construction of the project will provide an independent, objective existence of this theory, separate from both the theory of obligation, which was absorbed in the previous civil law and the theory of contract which is still mixed with it in the current civil law.
projet De Réforme Du Droit De La Responsabilité Civile-plrrc Urvoas 2017
Keywords: إصلاح نظرية المسؤولية المدنية، تنافسية المسؤولية المدنية، نظرية الالتزام، القانون المدني المقارن; Reform of Civil Responsibility Theory, Competitiveness of Civil Responsibility, Obligation Theory, Comparative Civil Law (PLRRC Urvoas 2017).